2016
DOI: 10.1080/15321819.2016.1209217
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of epidermal growth factor, latrophilin and seven transmembrane domain-containing protein 1 (ELTD1)viasiRNA-induced cell death in glioblastoma

Abstract: The failure of therapies targeting tumor angiogenesis may be caused by anti-angiogenic resistance mechanisms induced by VEGF and non-VEGF pathways alterations. Anti-angiogenic therapy failure is also attributed to immune system, acting by tumor-associated macrophages that release pro-angiogenic factors and a consequent increase of blood vessels. Recently, in a study by Rheal et al., a new angiogenic receptor, epidermal growth factor, latrophilin, and 7 trans-membrane domain-containing protein 1 on chromosome 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…ADGRL4/ELTD1 is not expressed by the majority of cancer cell lines [9]. However, it is expressed by glioblastomas where it possibly functions in a different way and is important for tumour survival, and is an emerging therapeutic target in this tumour type [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…ADGRL4/ELTD1 is not expressed by the majority of cancer cell lines [9]. However, it is expressed by glioblastomas where it possibly functions in a different way and is important for tumour survival, and is an emerging therapeutic target in this tumour type [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Through a global microarray meta-analysis (GAMMA), 39 we identified ELTD1, an angiogenic marker, to be highly expressed in high-grade gliomas and other groups have suggested that high ELTD1 expression levels may correlate with the aggressiveness of the glioma. 29,40 Previous studies have demonstrated that anti-ELTD1 treatments with pAb were effective in mouse GL261 and human G55 xenograft glioma models. 12 Other groups have also discovered that microRNA-139-5p directly binds onto and targets ELTD1 to inhibit cell proliferation in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…29 Therefore, we examined whether Notch levels changed with anti-ELTD1 treatment. 29 Therefore, we examined whether Notch levels changed with anti-ELTD1 treatment.…”
Section: Molecular-targeted Mris Of Representative Monoclonal An-mentioning
confidence: 99%
See 1 more Smart Citation
“…The level of VEGF in HGG is greater than 10-fold compared with LGG [83]. Thus, drugs have been developed to interfere with angiogenesis by directly blocking ligand (VEGF) or receptor (VEGFR) or by targeting proangiogenic molecules that function by alternative mechanisms [84]. Of all targeted biological agents, only bevacizumab (Avastin) has demonstrated efficacy.…”
Section: Emergent Treatments Strategiesmentioning
confidence: 99%